2017
DOI: 10.5603/ait.a2017.0069
|View full text |Cite
|
Sign up to set email alerts
|

Re-operative abdominal predictive score: a prognostic model combining Acute Re-intervention Predictive Index and intra-abdominal pressure

Abstract: Background: The decision to re-operate after abdominal surgery is still difficult, especially in the setting of intraabdominal sepsis. Mathematical models provide a good aid to both diagnosis and decision-making. Methods: A prospective observational study was conducted with 300 patients consecutively admitted to the intensive care unit of an academic institution affiliated to Calixto García Medical Faculty following abdominal surgery from January 2008 to January 2010. The patients were randomly separated (2:1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated that re-exploration of the abdomen after the first operation was associated with prolonged length of ICU stay, higher mortality rate and more frequent wound infections [31][32][33]. The most common causes of re-laparotomy were bleeding, sepsis, anastomotic leaks, bowel obstruction and wound dehiscence.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Several studies have demonstrated that re-exploration of the abdomen after the first operation was associated with prolonged length of ICU stay, higher mortality rate and more frequent wound infections [31][32][33]. The most common causes of re-laparotomy were bleeding, sepsis, anastomotic leaks, bowel obstruction and wound dehiscence.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…It has been claimed that with the proper use of ARPI, the surgical conundrum associated with the decision concerning reoperation of patients suspected with postoperative IAS can be resolved to a great extent [27]. ARPI is reported to be specifically useful in settings with limited resources [93]. In a cross-sectional, retrospective study of 94 patients diagnosed with abdominal sepsis, ARPI was used to assist in the decision process [23].…”
Section: Abdominal Reoperation Predictive Index (Arpi)mentioning
confidence: 99%